2020
DOI: 10.5114/ait.2020.93416
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temperature on volume, weight and density changes of i-gel masks

Abstract: The i-gel mask (Intersurgical, Wokingham, UK), is a second-generation, single-use supraglottic airway device. In contrast to other devices, its cuff consists of a thermoplastic elastomer (styrene-ethylenebutadiene-styrene) instead of an inflatable cuff. Previous studies have shown that over time the sealing improved over a period of 10 minutes compared to the moment of insertion [1, 2]. The sealing process may be based on various mechanisms. It is assumed that the warming from room to body temperature leads to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Martin et al revealed that all I-gel laryngeal masks have a significant temperature-dependent increase in volume and weight as well as a significant decrease in density. [40] These results may represent a new approach to explain how the prewarmed non-inflatable cuff laryngeal mask improves its sealing pressure over time after insertion. We found that a prewarming non-inflatable laryngeal mask could enable the cuff to fit the pharyngeal structure more quickly and improve the intubation success rate, which was confirmed by TSA.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Martin et al revealed that all I-gel laryngeal masks have a significant temperature-dependent increase in volume and weight as well as a significant decrease in density. [40] These results may represent a new approach to explain how the prewarmed non-inflatable cuff laryngeal mask improves its sealing pressure over time after insertion. We found that a prewarming non-inflatable laryngeal mask could enable the cuff to fit the pharyngeal structure more quickly and improve the intubation success rate, which was confirmed by TSA.…”
Section: Discussionmentioning
confidence: 86%
“…Martin et al revealed that all I-gel laryngeal masks have a significant temperature-dependent increase in volume and weight as well as a significant decrease in density. [ 40 ] These results may represent a new approach to explain how the prewarmed non-inflatable cuff laryngeal mask improves its sealing pressure over time after insertion.…”
Section: Discussionmentioning
confidence: 99%
“…Our meta-analysis found the sealing pressure of the prewarmed i-gel laryngeal mask was significantly higher than the control group. Martin et al 36 revealed that all i-gel mask has a significant temperature-dependent increase in volume and weight as well as a significant decrease in density. These results represent a new approach to explain how the prewarmed i-gel laryngeal mask improves its sealing pressure over time after insertion.…”
Section: Discussionmentioning
confidence: 99%